A pilot study of combined oral minocycline and narrowband UVB phototherapy in vitiligo: A randomized, double‐blind, placebo‐controlled trial. Issue 8 (1st June 2022) - Charoenpongpun, Namphet; Kamanamool, Nanticha; Udompataikul, Montree; Khunkhet, Saranya; Kanokrungsee, Silada
Abstract: Narrowband ultraviolet B (NBUVB) phototherapy is an effective therapeutic option for generalized vitiligo. Previous reports showed the potential benefit of minocycline to stop disease progression in vitiligo. Meanwhile, minocycline has antioxidative, anti‐inflammatory, and immunomodulating properties. There is no clinical study combining oral minocycline and NBUVB for treating generalized vitiligo. This study aims to compare the efficacy and safety of the combination treatment of NBUVB plus oral minocycline with NBUVB alone in generalized vitiligo. A randomized, double‐blinded, placebo‐controlled pilot study was conducted. Patients were randomly treated with either combined oral minocycline 100 mg per day plus NBUVB phototherapy or placebo plus NBUVB. All patients recieved NBUVB two times per week, for 12 weeks. The outcomes were assessed using Vitiligo Area Scoring Index score (VASI) percent change, quartile grading scale (QGS) of repigmentation, and Vitiligo Disease Activity Index (VIDA) score. Fourteen generalized vitiligo patients were included, and seven cases were assigned in each group. At week 12, the mean VASI score was decreased by 28.87% (24.15) in the minocycline group compared to 27.26% (7.98) in placebo group ( p  = 0.886). No significant difference was observed between both treatment modalities in QGS of repigmentation and mean VIDA score change. Two of the seven patients (29%) receiving minocycline developed hyperpigmentation, dark‐brown and muddy brown discoloration, which was only confined to some vitiliginous patches. In conclusion, combination therapy with oral minocycline does not enhance the efficacy of NBUVB in generalized vitiligo. Due to the high incidence of drug‐induced skin hyperpigmentation, minocycline plus NBUVB should be avoided.